Adaptation to the market? Status differences between target occupations in the application process and realized training occupation of German adolescents - Schels, Brigitte; Abraham, Martin (Journal of Vocational Education and Training, 2023)
Adolescents’ occupational expectations are relevant for occupational status attainment. In strong vocational education and training (VET) systems, such as in Germany, school leavers face the challenge of forming occupational expectations that correspond to the competitive VET market. This study investigates students’ target occupations in the application process and its relation to their first training occupation. Do applicants for VET positions apply for occupations of different socioeconomic status over time? Does the status of the target occupations increasingly fit to the finally achieved training occupation? Are there differences by familial socioeconomic background? Analysis are based on longitudinal data on the application process collected from German students in lower secondary and intermediate secondary schools in one urban area. Overall, the status level of the target occupations at the beginning of the application process differs significantly according to school track, but additionally to school grades or family background. At the end of the application process, the application behaviour becomes diversified: applicants with poor school grades and of low status continue to apply for target occupations at a similar status level but at the same time apply for occupations of relative lower status. This lower level does not, however, translate into training occupation